Kupirovanie kliniceskich projavlenij osteochondroza pozvonocnika u sportsmenov metodom iglorefleksoterapi - Shestakov, V. Ya.; Artemenkov, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article analyzes the features of manifestations of osteochondrosis of the spine in athletes and the methods used to treat it. Objective: to conduct an acupuncture diagnosis of the state of the nervous system of athletes and stop the clinical manifestations of osteochondrosis using acupuncture. The experiment was conducted on 10 athletes - weightlifters, gymnasts and athletes. To stop the clinical manifestations of osteochondrosis, the corporal acupuncture method was applied according to a set of points, anatomically related to certain functional systems. It is shown that acupuncture allows you to effectively correct the conditions caused by dysfunction of the autonomic and somatic systems. Stimulation in this group of patients with a wide spectrum of action, exerting their influence through the reticular formation of the brain stem on vascular and muscle tone, affects the emotional sphere and increases the general resistance of the body and metabolic processes After the first course of treatment, improvement occurred in 80% of patients, after the second - in 100%.